Influence of the Hfq and Crc global regulators on the control of iron homeostasis in Pseudomonas putida. (5th August 2018) - Sánchez‐Hevia, Dione L.; Yuste, Luis; Moreno, Renata; Rojo, Fernando
Summary: Metabolically versatile bacteria use catabolite repression control to select their preferred carbon sources, thus optimizing carbon metabolism. In pseudomonads, this occurs through the combined action of the proteins Hfq and Crc, which form stable tripartite complexes at target mRNAs, inhibiting their translation. The activity of Hfq/Crc is antagonised by small RNAs of the CrcZ family, the amounts of which vary according to carbon availability. The present work examines the role of Pseudomonas putida Hfq protein under conditions of low‐level catabolite repression, in which Crc protein would have a minor role since it is sequestered by CrcZ/CrcY. The results suggest that, under these conditions, Hfq remains operative and plays an important role in iron homeostasis. In this scenario, Crc appears to participate indirectly by helping CrcZ/CrcY to control the amount of free Hfq in the cell. Iron homeostasis in pseudomonads relies on regulatory elements such as the Fur protein, the PrrF1‐F2 sRNAs, and several extracytoplasmic sigma factors. Our results show that the absence of Hfq is paralleled by a reduction in PrrF1‐F2 small RNAs. Hfq thus provides a regulatory link between iron and carbon metabolism, coordinating the iron supply to meet the needs of the enzymes operational under particular nutritional regimes.